Validating the Indonesian Connor-Davidson Resilience Scale: Confirmatory Factor Analysis in Surakarta High School Students - Priyatama, Aditya Nanda; Putri, Nawangsari Indah Kusuma; Safira, Flaviana Ursula Nadia Gusti Yunan; Widiantama, Luhuring Budi; Ni’matussholihah, Nadyah; Yuliana, Nada Citra; Satwika, Pratista Arya (Journal of Educational, Health and Community Psychology, 2025)
Resilience is a crucial aspect that is closely related to the mental health of children and adolescents. The development of measurements related to resilience can be the first step to be able to conduct accurate psychological assessments and develop strategies to strengthen resilience. This study aims to evaluate the validity and reliability of the Indonesian version of the Connor-Davidson Resilience Scale (CD-RISC) using Confirmatory Factor Analysis (CFA). The analysis was conducted on a sample of 1,087 high school students from the Surakarta area. The initial CFA model for the resilience scale showed a good fit (RMSEA = 0.073; SRMR = 0.055; CFI = 0.94, NFI = 0.95, GFI = 0.90).  Model fit means that the Connor-Davidson Resilience Scale (CD-RISC) model is supported by empirical data and supports the theoretical structure. The scale also met the criteria of convergent and discriminant validity, as well as reliability, in explaining the dimensions of resilience: personal competence, trust in instinct, acceptance of change, control, and spirituality.  Among these dimensions, spirituality, personal competence, and trust had the highest reflective weight, followed by acceptance and control. In conclusion, this study confirmed that the Indonesian version of the Connor-Davidson Resilience Scale (CD-RISC) is a valid and reliable tool for measuring resilience among senior high school students. Therefore, this scale can be used in conducting accurate psychological assessments in order to build strategies to strengthen resilience in adolescents.